Phenotypic Effect of α‐Globin Gene Numbers on Indian Sickle β‐Thalassemia Patients. Issue 2 (6th January 2014) - Pandey, Sanjay Kumar; Pandey, Sweta; Ranjan, Ravi; Shah, Vineet; Mishra, Rahasya Mani; Sharma, Monica; Saxena, Renu
<x xml:space="preserve">Abstract</x> Background Sickle cell β‐thalassemia is a compound heterozygous state of β‐thalassemia and sickle cell anemia. Patient with these conditions showed mild‐to‐severe clinical phenotype. Objectives The objective of this study was to evaluate the effects of α‐globin gene numbers on the phenotype of sickle cell β‐thalassemia patients. Materials and Methods Seventy‐five sickle cell β‐thalassemia patients were characterized. Clinical, hematological, and molecular characterization was performed in all subjects. Amplified refectory mutation system–polymerase chain reaction was applied for β‐thalassemia mutation study while α‐genotyping was conducted by Gap‐PCR. Results Highest frequency of IVS1–5 (33 out of 75 patients) β‐thalassemia genotype was recorded. Twenty‐eight patients were reported with α‐globin chain deletion while four had α‐triplications (Anti α‐3.7kb). Sickle β‐thalassemia patients with α‐chain deletions ameliorate hematological and clinical variables. Conclusions This study indicates that the coexistence of α‐globin chain deletions showed mild phenotype instead of absence of α‐chain deletions while the patients with triplication of α‐genes express severe phenotype.